Ex situ conservation of Rubus L. (Rosaceae) genetic resources (a review) - S. E. Dunaeva; L. S. Krasovskaya; T. A. Gavrilenko (Труды по прикладной ботанике, генетике и селекции)
This review examines the issues of ex situ conservation of Rubus L. genetic resources in the world’s genebanks and various institutions in different countries. The most urgent among the studied problems are the issues of preserving interspecific and intraspecific diversity and its sustainable utilization in breeding programs. The main attention is paid to pomologically important subgenera – raspberries Idaeobatus Focke (= Batidaea (Dumort.) Greene) and blackberries Rubus (= Eubatus Focke).Detailed information is provided on the composition and size of field, in vitro and cryogenic collections as well as seed collections. Specific features of conserving the genus’s genetic resources in collections of different types are analyzed. Information on collections of the genus preserved in the Russian Federation, unavailable in international databases, is summarized. Particular attention is paid to the collection of raspberries and blackberries held by the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR), including the history of its formation and the current state.VIR’s clonal genebank currently preserves 359 accessions of Rubus L., belonging mainly to the subgenera of raspberries (Idaeobatus) and blackberries (Rubus): 209 of these accessions are maintained in the field collection, and 150 in the in vitro collection. Raspberry cultivars developed through breeding dominate in the VIR collection – 170 accessions, among which 126 have been released by domestic breeders. Wild species are mainly represented by those collected in the Russian North – 49 clones of red raspberry (Rubus idaeus L.) and 6 of cloudberries (R. chamaemorus L.) – and in the Caucasus (35 accessions of 26 species). The data on the species diversity of the genus in Russian natural flora are presented and the strategy of replenishment, study and conservation of Rubus L. genetic resources at VIR’s genebank is discussed.